2018
DOI: 10.1088/1755-1315/173/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Dust pollution and its potential health risk exposure to inhabitants of Covenant University and canaanland, Ogun state, Nigeria

Abstract: Abstract. Understanding the background concentration of heavy metals in dust samples is so much important for identifying and managing pollution. Thus, these concentrations in dust can be distributed indoors and outdoors in order of magnitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Among the four (4) heavy metals considered, the degree of pollution caused by Ni and Cr during these two seasons changed significantly, but those of Pb and Zn did not change. It was also observed that the deeper subsurface lithofacies in this area of study contain high concentrations of the heavy metals 38,39 . The degree of pollution in these different lithofacies, increased from layer 1 up to layer 5.…”
Section: Geo-accumulation Index Resultsmentioning
confidence: 60%
“…Among the four (4) heavy metals considered, the degree of pollution caused by Ni and Cr during these two seasons changed significantly, but those of Pb and Zn did not change. It was also observed that the deeper subsurface lithofacies in this area of study contain high concentrations of the heavy metals 38,39 . The degree of pollution in these different lithofacies, increased from layer 1 up to layer 5.…”
Section: Geo-accumulation Index Resultsmentioning
confidence: 60%